Chemical composition and protein quality of mortadella formulated with carbon monoxide-treated porcine blood - Fontes, Edimar A. F.; Fontes, Paulo R.; Gomide, Lúcio A. M.; Costa, Neuza M. B.; Peternelli, Luiz A.; Ramos, Eduardo M. (LWT - Food Science and Technology, 2015)
Porcine blood may be used in meat processing as source of protein for human consumption. This study aimed to analyze the chemical composition and protein quality (chemical score, protein digestibility-corrected amino acid score, digestibility, and protein efficiency) of mortadellas formulated by replacing different levels (0, 5, 10, 15 and 20%) of meat by carbon monoxide-treated (CO-treated) porcine blood. The mortadellas showed chemical score above 1, digestibility values above 90% and their protein digestibility corrected amino acid score (PDCAAS) did not differ (P > 0.05). The protein efficiency ratio (PER) and the net protein ratio (NPR) values of the mortadella diets did not differ from those of the casein control diet. It is concluded that, regardless of the level of blood addition, mortadellas have high protein quality and digestibility. Therefore, from the nutritional point of view, meat replacement with up to 20% of CO-treated blood is nutritionally adequate for being used in sausage production.
Keywords: Porcine blood; Carbon monoxide; Protein quality; Digestibility